Beyond timber: making multiple use forest management a reality in Central Africa forests - Nasi, Robert (Stellenbosch University, 2011)
Multiple-use forest management is considered by many as a preferable alternative to singleuse (generally timber-dominant) management models. In the Congo Basin, integration of timber and non-timber forest resources plays a key role in the subsistence and market economies of rural communities, enhancing their well-being and reducing economic risk. This is however largely happening as an informal sector economy. Managing for multiple use in “legal” designated land-use types (industrial logging concessions, protected areas or cashcrop plantations) appears hampered by the spatial overlap of different interests and bargaining power, the multiple-uses of some favorite timber species, inadequate institutional support, inappropriate policies and incentives, poor law enforcement and unclear (or at least unrecognized) tenure and use rights. This paper explores the main land-use and management models in Central Africa. Most of the current land-use types and associated management models focus on only one or two goods or services in one management unit while, for the most advanced, trying as much as possible to reduce disturbance and degradation of the other non-managed forest goods and services. The only ‘true’ multiple-use management system appears to be traditional shifting cultivation but this is not a forest land use and it induces important changes in the flora and fauna. A few promising but yet ‘unfinished’ examples of multiple-use management models do exist. We contend however that true multiple-use could be realized through new innovative land-use units, integrated production and conservation territories, allowing a spatial cohabitation of the interests of local people, conservation proponents and extractive industries in the same land-use unit.